Efektivitas Pemberian Edukasi Stunting Terhadap Pengetahuan Ibu di Kampung Bius Kecamatan Silih Nara Kabupaten Aceh Tengah - Silfia Siska; Fauzi Ali Amin; Riza Septiani (Pelantar Press, 2025)
Mothers' knowledge is very influential in preventing stunting because their ability to support optimal child growth and development, recognize signs of growth disorders, and provide proper nutritional intake is very important. Efforts to educate children about nutrition and health can be done with various methods including lectures and role play and lecture methods. This study aims to determine the effectiveness of stunting education using lecture and role play methods on mothers' knowledge about stunting in toddlers in Kampung Bius, Silih Nara District, Central Aceh Regency. The research method used a quasi-experimental with a two-group design. Education was carried out in 2 methods, namely lectures, with a total of 30 mothers who have toddlers as participants, and role play methods with a total of 16 mothers who have toddlers as participants. Data analysis used a paired T-test. The results showed that the role play group before being given an average score of 18.50 with range 10-24) and after being given it became 21.20 with range 15-25. While in the lecture group before being given an average score of 15.66 with range 5-22 and after being given it became 23.23 with range 18-25. The statistical test obtained in the role play group had a p-value of 0.004, indicating a difference before and after stunting education on improving mothers' knowledge. In the lecture group, the p-value was 0.001, indicating a difference before and after stunting education on improving mothers' knowledge. It can be concluded that the lecture method is more effective in improving mothers' knowledge about stunting prevention than the role play method. It is hoped that health workers at the Community Health Center can use the lecture method to improve mothers' knowledge about toddler stunting